Pengembangan Wisata Kuliner Kearifan Lokal Berkelanjutan Di Kabupaten Cirebon - Yati, Yati; Rizkiwati, Baiq Yuliana (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Cirebon Regency is an area rich in tourism, both culinary, religious and cultural tourism. Culinary with local wisdom which has become an icon and has its own uniqueness and characteristics is the basis for developing amidst the international culinary ceasefire. The development of culinary tourism based on local wisdom in Cirebon Regency has great potential to improve the local economy and preserve local culture and traditions. This article aims to identify the potential and challenges in developing sustainable culinary tourism in Cirebon Regency. The method used in this research is a qualitative approach with in-depth interviews and field observations. The research results show that Cirebon has various types of typical food that can be used as tourist attractions. However, there are several challenges that must be faced, such as the lack of unrepresentative dining facilities and the people's westernized lifestyle. Collaboration between the government, community and the private sector is very necessary to create sustainable culinary tourism in Cirebon. The SWOT analysis shows that the strengths and opportunities in developing culinary tourism in Cirebon can be utilized to overcome existing weaknesses and threats